Identification of Risk Factors for Stroke in China: A Meta-Analysis of Prospective Cohort Studies - Yuan, Weizhuang; Wu, Bo; Lou, Min; Song, Bo; Han, Xiang; Sheng, Feng; Xu, Weihai (Frontiers in Neurology, 2022)
This study aimed to identify independent risk factors for first occurrence of stroke in Chinese individuals based on prospective cohort studies. Forty prospective cohort studies assessing 1,984,552 individuals were selected for the final meta-analysis. The identified risk factors for stroke in the Chinese population included old age (RR=1.86, 95%CI: 1.47-2.36), hypertension (RR=2.76, 95%CI: 2.26-3.37), cardiovascular disease history (RR=1.98, 95%CI: 1.06-3.69), chronic kidney disease (RR=1.65, 95%CI: 1.36-2.01), diabetes mellitus (RR=1.71, 95%CI: 1.34-2.18), metabolic syndrome (RR=1.59, 95%CI: 1.33-1.90), hyperglycemia (RR=1.49, 95%CI: 1.31-1.69), obesity (RR=1.45, 95%CI: 1.29-1.63), smoking (RR=1.42, 95%CI: 1.27-1.58), prolonged sleep time (> 7.5 hours, RR=1.44, 95%CI: 1.19-1.75), higher levels of triglyceride (RR=1.19, 95%CI: 1.07-1.32), C-reactive protein (RR=1.34, 95%CI: 1.07-1.69). High fruit-rich diet (RR=0.68, 95%CI: 0.58-0.80) was associated with a lower risk of stroke. The spectrum and power of risk factors differed between different cohort inclusion years. These findings provide a comprehensive tool for the primary prevention of stroke in Chinese individuals.